Weight and performance optimization of rectangular staggered fins heat exchangers for miniaturized hydraulic power units using genetic algorithm. (December 2021) - Zhang, Yayun; Peng, Jinghui; Yang, Rui; Yuan, Lipeng; Li, Songjing
Abstract: The compact, lightweight, and energy-efficient heat exchanger is significant for the miniaturization of hydraulic power unit in quadruped robot. In this work, a rectangular staggered fins heat exchanger (RSFHE) as an ideal lightweight heat exchanger for miniaturized hydraulic power units is investigated and optimized based on the experimental correlations of heat transfer and flow resistance for the fluids with different Prandtl number. Function models including the related mass, outlet temperature and pressure drop are defined. A sensitivity analysis is presented to investigate the effect of key parameters on function models, which can evaluate the contributions of variables to the comprehensive performance of the heat exchanger. Based on these function models, the heat exchanger key parameters are optimized using genetic algorithm (GA). Moreover, numerical simulations are conducted to explore the thermal-hydraulic performance of the original and optimized heat exchangers and the simulation results are almost equal to the theoretical results calculated by experimental correlations. Compared with the original heat exchanger, the total weight of the optimized exchanger reduces by 25.49% and its heat transfer capacity increases by 24.22% taking the inlet-outlet temperature difference of the hydraulic oil as the index, which is a great improvement for the miniaturization and lightweight of the hydraulic power unit.